Bismuth coated graphite felt modified by silver particles for selective electroreduction of CO2 into formate in a flow cell. (1st March 2021) - Lou, Yaoyin; Fu, Dong; Fabre, Bruno; Fourcade, Florence; Amrane, Abdeltif; Pasturel, Mathieu; Bourzami, Riadh; Merdrignac-Conanec, Odile; Labasque, Thierry; Geneste, Florence
Highlights: A new Bi-coated graphite felt decorated with silver particles was prepared. The parameters of the spontaneous deposition were optimized to achieve a homogenous material. The bimetallic electrode exhibited high selectivity of 88% for formate production. Ag and Bi played a complementary role instead to perform competitive reactions. The high performance of the electrode evidenced its potential for CO2 reduction. Abstract: A 3D porous Ag-Bi electrode was developed to achieve the highly selective reduction of CO2 into formate. Ag particles were deposited on Bi coated graphite felt by galvanic displacement reaction. The selectivity of the reduction was enhanced with the Ag-Bi electrode compared with Bi coated graphite felt. The bimetallic catalytic system converted CO2 into formate with a high selectivity of 88% at -1.6 VSCE . The highly porous structure and large surface area of the electrode facilitated the mass transport, leading to a high surface current density of 76 mA cm −2 and a production rate of 8.1 ± 0.4 mmol cm −3 h −1 (62 ± 3 mg cm −2 h −1 ). These results are very promising in the context of the electrochemical conversion of CO2 . Graphical abstract: Image, graphical abstract